Converting Technologies for Mobile Internet Application Based on HTML5 - Huiyun Li; Xinzhang Yang; Wensheng Hu; Jinjun Wen (Dianxin kexue, 2013)
The proposed HTML5 standard makes web applications’ ability be enhanced，and many functions that originally need many plug-ins to support can be realized directly in HTML. HTML5 becomes a new solution for mobilization. New features of HTML5 for mobile devices were described first，and then the converting technologies were expounded from web portals for PC to web applications for mobilephones. In the end，the converting effects and realization difficulties were summarized.